1999
DOI: 10.1159/000014093
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Changes of Leptin Levels in Full-Term and Preterm Neonates: Their Relation to Intrauterine Growth, Gender and Testosterone

Abstract: The present study was carried out to investigate leptin levels in arterial and venous cord serum and in amniotic fluid in full-term infants at birth and on the 5th postnatal day to define the relationship of leptin to intrauterine growth rate, gender and early postnatal life. The relation of weight gain to serum leptin levels in male preterm infants was determined measuring leptin concentration weekly in the first 5 postnatal weeks. Testosterone levels were determined simultaneously to explore a possible relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
50
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(59 citation statements)
references
References 31 publications
8
50
1
Order By: Relevance
“…In this study, cord leptin levels were markedly higher in female than in male infants, and this difference was independent of birth weight and gestational age. Although the sexual dimorphism in leptin levels becomes most apparent at the onset of puberty, a significant gender difference in leptin levels at birth has previously been reported by some (9,(15)(16)(17)(18), but not all studies (12,20). It is discussed that these gender differences might reflect the transient perinatal elevation in sex steroids, as estrogens are associated with higher leptin concentrations, while androgens are inversely related to leptin levels (18).…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…In this study, cord leptin levels were markedly higher in female than in male infants, and this difference was independent of birth weight and gestational age. Although the sexual dimorphism in leptin levels becomes most apparent at the onset of puberty, a significant gender difference in leptin levels at birth has previously been reported by some (9,(15)(16)(17)(18), but not all studies (12,20). It is discussed that these gender differences might reflect the transient perinatal elevation in sex steroids, as estrogens are associated with higher leptin concentrations, while androgens are inversely related to leptin levels (18).…”
Section: Discussionmentioning
confidence: 80%
“…Although the sexual dimorphism in leptin levels becomes most apparent at the onset of puberty, a significant gender difference in leptin levels at birth has previously been reported by some (9,(15)(16)(17)(18), but not all studies (12,20). It is discussed that these gender differences might reflect the transient perinatal elevation in sex steroids, as estrogens are associated with higher leptin concentrations, while androgens are inversely related to leptin levels (18). Not consistent with these observations, Matsuda et al (12) reported that serum concentrations of estradiol and testosterone did not differ between male and female neonates and did not correlate with leptin concentration suggesting that the existence of this gender difference in the fetus might also depend on genetic factors.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Higher leptin levels can be found in babies with diabetic mothers. There is increased accumulation of adipose tissue, which is characteristic for such infants (12,13). The serum leptin level reveals that the level of nutrition is equal to the level of hormones.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that leptin contributes to a physiological pregnancy by regulation of implantation, energy balance of placenta and conceptus, as well as an angiogenic factor (14 -16). During pregnancy, leptin expression undergoes dramatic changes in maternal plasma in parallel with the rising of cytokine levels during the first trimester (17) returning to normal levels after delivery (18). The production of placental leptin is reported to be increased by interleukin-1a, 17b-estradiol and hypoxia (19 -21).…”
Section: Introductionmentioning
confidence: 99%